Tingkat Pengetahuan Ibu Primigravida dalam Pengasuhan Bayi Baru Lahir - Adzra Nabilla; Edwina R. Monayo; Dewi S. Hiola (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe primigravida mothers' knowledge of newborn care at the Kabila Community Health Center in Bone Bolango Regency. This study used a non-experimental, quantitative design with descriptive methods and involved 31 primigravida respondents. The results showed that 17 primigravida mothers (55%) had a good level of knowledge, but 4 respondents (13%) had poor knowledge. The conclusion is that while most primigravida mothers have a good level of expertise in newborn care, some still have gaps in their understanding, necessitating increased education and ongoing support from health workers. Keywords: Primigravida Mothers, Neonatal, Newborn Care, Knowledge